Misi Gereja Melalui Pendidikan di Sekolah: Sebuah studi kasus di SMAK Dempo, Malang - Antonius; Suwito, Benny (Perspektif, 2009)
The missionary role of the church, inherited from Jesus Christ, touches every aspect of human life. The mission is not just a matter of spiritual growth, but also deals with all social development. Therefore, the Catholic church in Indonesia considers education as a missionary priority. There are many good Catholic schools around the country that earn good reputation. However, the crisis of identity seems to emerge inside these many institutions. The authors raise the question, whether currently the church is really doing the missionary job, i.e. proclaiming the Good News, through these schools, or simply running schools with Catholic label. A case studi at SMAK Dempo, Malang, is presented as an ilustration of this concern. The goal is to remind the church about the basic idea of running schools as a tool of missionary ministry.